Efficient and stable quasi-plane organic solar cell and preparation method thereof

By using hindered phenolic antioxidants and specific additives in the active layer of organic solar cells, combined with continuous spin coating method, the problem of difficult to take into account both the internal stability and morphological stability of the active layer is achieved, and efficient and stable quasi-planar organic Solar cells with high stability and high photoelectric properties.

CN119403342AActive Publication Date: 2025-02-07JIANGXI NORMAL UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411391588.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-02-07
Estimated Expiration
2044-10-08

AI Technical Summary

Technical Problem

The active layer of existing organic solar cells is difficult to take into account both internal stability and morphological stability, making it difficult for devices to take into account both high stability and high photoelectric properties.

Method used

The hindered phenolic antioxidant is used as an additive and the continuous spin coating method to form an active layer with high intrinsic stability and morphological stability. The specific method includes adding hindered phenolic antioxidants to the polymer donor and adding specific additives to the non-fullerene acceptors, forming an active layer with a thickness of 100-150 nm by spin coating.

Benefits of technology

It significantly improves the stability and photoelectric performance of organic solar cells, achieves an energy conversion efficiency of 19.03%, and significantly improves the prospects of the device commercialization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119403342A_ABST
    Figure CN119403342A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of organic solar cells, and discloses an efficient and stable quasi-plane organic solar cell and a preparation method thereof. The efficient and stable quasi-plane organic solar cell comprises a transparent conductive substrate, a hole transport layer, an active layer, an electron transport layer and a metal cathode layer from bottom to top, the active layer comprises a polymer donor layer which is spin-coated on the hole transport layer and added with a hindered phenol antioxidant, and a non-fullerene acceptor layer which is spin-coated on the polymer donor layer and contains an additive. According to the application, a strategy of combining a hindered phenol antioxidant as an additive with a continuous spin-coating method is adopted to obtain an active layer with high internal stability and morphology stability, so that an organic solar cell with high stability and high photoelectric property is obtained. According to the organic solar cell prepared by the invention, the efficiency is remarkably improved to 19.03%, and the organic solar cell is excellent in stability and has a good commercialization prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of organic solar cells, and in particular to a highly efficient and stable quasi-planar organic solar cell and a preparation method thereof. Background Art

[0002] As a new photovoltaic technology, organic solar cells have attracted more and more attention due to their advantages such as low cost, light weight, flexibility, solvent processing and large-area printing. At present, researchers have made continuous progress in the understanding of the mechanism of organic solar cells, the design and synthesis of active layer materials, and morphology control. The energy conversion efficiency of single-junction organic solar cells exceeds 19%.

[0003] Continuous breakthroughs in device efficiency have greatly increased the potential for commercialization of organic solar cells. However, the issue of device stability remains crucial to its future commercial viability. In general, the stability of the active layer plays a decisive role in the life of organic solar cells and is mainly affected by two factors. On the one hand, the intrinsic stability of the active layer materials under conditions such as light, heat, water and oxygen is poor. Some studies have shown that high-energy ultraviolet rays can induce polymer molecules to react with oxygen to produce superoxide radicals, or energy is transferred from the triplet exciton of the polymer to molecular oxygen to form singlet oxygen; when electrons are transferred from the donor to the acceptor, if the lowest unoccupied molecular orbital energy level of the acceptor is relatively shallow, the electrons are more likely to react with oxygen to form superoxide anions. Active species such as superoxide radicals, singlet oxygen and superoxide anions generated in the active layer will irreversibly decompose the donor and acceptor molecules, especially initiating chain scission reactions of the polymer donor, resulting in donor degradation and significant degradation of device performance. In addition, in the active layer system based on polymer donors and Y6-type acceptors, the photostability of the polymer donor is significantly poor and it is more susceptible to photobleaching under light. Currently, UV filters, UV absorbers or antioxidants are commonly used to inhibit photoaging and improve device stability. However, these methods usually only bring minimal performance improvements or even require sacrificing device performance to a certain extent.

[0004] On the other hand, the morphological stability of the active layer is also insufficient. High-efficiency bulk heterojunction (BHJ) devices are usually formed by mixing electron donor and acceptor materials, and their morphology is often in a non-thermodynamic equilibrium state. Due to the different glass transition temperatures of the donor and acceptor, their diffusion coefficients are also different. Therefore, under light or heat conditions, the donor and acceptor tend to re-aggregate and form excessive phase separation, namely the "island effect", which significantly reduces the exciton dissociation and charge collection efficiency, and ultimately reduces the stability of the device.

[0005] At present, methods to improve the stability of the active layer include forming a quasi-planar heterojunction (PPHJ) morphology through the sequential deposition of donors and acceptors, or developing an all-polymer active layer to reduce entropy and improve morphological stability. Although these studies have improved the morphological stability to a certain extent, the research on improving the intrinsic stability and morphological stability of the active layer at the same time is still relatively limited, making it difficult to simultaneously improve the stability and optoelectronic performance of the device. Summary of the invention

[0006] The present application provides a highly efficient and stable quasi-planar organic solar cell and a preparation method thereof, aiming to solve the problem that the active layer of existing organic solar cells is difficult to balance intrinsic stability and morphological stability, resulting in the organic solar cell being difficult to balance high stability and high photoelectric performance.

[0007] In order to achieve the above objectives, the present application adopts the following technical solutions.

[0008] In a first aspect of the present application, a highly efficient and stable quasi-planar organic solar cell is provided, which comprises, from bottom to top, a transparent conductive substrate, a hole transport layer, an active layer, an electron transport layer and a metal cathode layer;

[0009] The active layer includes a polymer donor layer with a hindered phenol antioxidant added thereto, which is spin-coated on a hole transport layer, and a non-fullerene acceptor layer containing an additive, which is spin-coated on the polymer donor layer.

[0010] Preferably, the polymer donor is any one of PM6, PM7 or D18;

[0011] The non-fullerene acceptor is BTP-eC9 or L8-BO;

[0012] The hindered phenol antioxidant is any one of antioxidants AO1010, AO245 or AO3114;

[0013] The additive is 1,8-diiodooctane or 1,3-dibromo-5-chlorobenzene.

[0014] Preferably, the amount of the hindered phenol antioxidant is 2-8 wt % of the amount of the polymer donor.

[0015] Preferably, the thickness of the active layer is 100-150 nm.

[0016] Preferably, the transparent conductive substrate is ITO glass;

[0017] The hole transport layer material is 2PACz;

[0018] The metal cathode layer material is Ag or Al;

[0019] When the non-fullerene acceptor is BTP-eC9, the electron transport layer material is PFN-Br, and the additive is 1,8-diiodooctane;

[0020] When the non-fullerene acceptor is L8-BO, the electron transport layer material is PDINN, and the additive is 1,3-dibromo-5-chlorobenzene.

[0021] The second aspect of the present application provides a method for preparing the above-mentioned efficient and stable quasi-planar organic solar cell, comprising:

[0022] S1, after cleaning the transparent conductive substrate, spin-coating an ethanol solution with a concentration of 2PACz on the surface of the substrate, and annealing the substrate to form a hole transport layer;

[0023] S2, dissolving the polymer donor and the hindered phenol antioxidant in chloroform to prepare a donor solution;

[0024] BTP-eC9 and 1,8-diiodooctane were dissolved in chloroform to prepare acceptor solution A. The donor solution was first spin-coated on the surface of the hole transport layer, and then the acceptor solution A was spin-coated on the surface of the hole transport layer. After annealing, an active layer A was obtained.

[0025] or,

[0026] L8-BO and 1,3-dibromo-5-chlorobenzene were dissolved in chloroform to prepare acceptor solution B. The donor solution was first spin-coated on the surface of the hole transport layer, and then the acceptor solution B was spin-coated on the surface of the hole transport layer. After annealing, an active layer B was obtained.

[0027] S3, dissolving PFN-Br in methanol to prepare an electron transport material solution A, and spin coating the solution on the surface of the active layer A to form an electron transport layer;

[0028] Alternatively, PDINN is dissolved in methanol to prepare an electron transport material solution B, and the solution is spin-coated on the surface of the active layer B to form an electron transport layer;

[0029] S4, evaporating a metal conductor on the surface of the electron transport layer to form a metal cathode layer, thereby obtaining a quasi-planar organic solar cell.

[0030] Preferably, the spin coating speed of the donor solution in S2 is 2000-2500 rpm, and the spin coating time is 30-40 s;

[0031] The spin speed of the receptor solution A or receptor solution B is 1500-2000 rpm, and the spin coating time is 30-40 s;

[0032] The annealing temperature is 90-100°C, and the annealing time is 5-10 minutes.

[0033] Preferably, the spin coating speed of the 2PACz ethanol solution in S1 is 3000 rpm, and the spin coating time is 30 s; the annealing temperature is 80-90° C., and the time is 3-5 min;

[0034] The spin coating speed of the electron transport material solution A or the electron transport material solution B in S3 is 3000-3500 rpm, and the spin coating time is 30-40 s.

[0035] Preferably, the concentration of the 2PACz ethanol solution is 0.1-1.0 mg / mL;

[0036] In the donor solution, the total concentration of the polymer donor and the hindered phenol antioxidant is 6-10 mg / mL;

[0037] In the receptor solution A, the concentration of BTP-eC9 is 6-12 mg / mL;

[0038] In the receptor solution B, the concentration of L8-BO is 8-12 mg / mL;

[0039] In the electron transport material solution A, the concentration of PFN-Br is 0.1-1.0 mg / mL;

[0040] In the electron transport material solution B, the concentration of PDINN is 0.1-1.0 mg / mL;

[0041] Preferably, the volume of the 1,8-diiodooctane is 0.25-0.5% of the volume of the receptor solution A;

[0042] In the receptor solution B, the concentration of 1,3-dibromo-5-chlorobenzene was 10-15 mg / mL.

[0043] Compared with the prior art, the beneficial effects of this application are:

[0044] The present application adopts a strategy of combining hindered phenolic antioxidants as additives with a continuous spin coating method to obtain an active layer with high intrinsic stability and morphological stability, and then obtains a quasi-planar organic solar cell with high stability and high photoelectric performance. On the one hand, hindered phenolic antioxidants have multiple hydroxyl binding sites, which can react highly with superoxide radicals, thereby quenching free radicals and terminating free radical-induced chain degradation reactions, thereby improving the intrinsic stability of the material; on the other hand, hindered phenolic antioxidants have excellent thermal stability and obvious steric hindrance, which can prevent excessive aggregation of donor and acceptor materials, thereby improving morphological stability. In addition, hindered phenolic antioxidants have a synergistic effect with the commonly used donor PM6. The multiple hydroxyl groups in the hindered phenolic antioxidants are easy to form hydrogen bonds with the fluorine atoms in the donor PM6, thereby enhancing the interaction between molecules, increasing the crystallinity of PM6, making the molecular stacking more orderly, and improving the vertical phase separation morphology, which is conducive to charge separation and transmission.

[0045] The quasi-planar organic solar cell prepared in the present application has a significantly improved efficiency to 19.03% and has excellent stability and has good commercial prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments recorded in the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0047] Figure 1 UV-visible absorption spectra of polymer donor PM6, non-fullerene acceptors BTP-eC9 and L8-BO, and antioxidant AO1010;

[0048] Figure 2 Graphs showing current-voltage curves of the quasi-planar organic solar cells of Example 2 and Comparative Example 1;

[0049] Figure 3 is a current-voltage curve diagram of the quasi-planar organic solar cell of Example 4 and Comparative Example 2;

[0050] Figure 4 It is a normalized graph of energy conversion efficiency of the quasi-planar organic solar cells of Example 4 and Comparative Example 2. DETAILED DESCRIPTION

[0051] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0052] In the following description of this embodiment, the terms "include", "comprising", "having" and "containing" are all open terms, meaning including but not limited to.

[0053] In the following description of this embodiment, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist at the same time. A and B can be singular or plural. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.

[0054] In the following description of this embodiment, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0055] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0056] Those skilled in the art should understand that in the following description of the embodiments of the present application, the order of serial numbers does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0057] Those skilled in the art will appreciate that the numerical ranges in the embodiments of the present application are to be construed as specifically disclosing each intermediate value between the upper and lower limits of the scope. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present application. The upper and lower limits of these smaller ranges may be independently included or excluded in the scope.

[0058] Unless otherwise specified, the technical / scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which this application belongs. Although this application only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of this application. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0059] In a first aspect, the present application provides a highly efficient and stable quasi-planar organic solar cell, which comprises, from bottom to top, a transparent conductive substrate, a hole transport layer, an active layer, an electron transport layer and a metal cathode layer;

[0060] The active layer includes a polymer donor layer with a hindered phenol antioxidant added thereto, which is spin-coated on a hole transport layer, and a non-fullerene acceptor layer containing an additive, which is spin-coated on the polymer donor layer.

[0061] In the present application, the polymer donor is any one of PM6, PM7 or D18; the non-fullerene acceptor is BTP-eC9 or L8-BO; the hindered phenol antioxidant is any one of antioxidants AO1010, AO245 or AO3114. AO1010 is preferred. Among them, the polymer donor is preferably PM6, and the hindered phenol antioxidant is preferably AO1010. Specifically, the chemical structures of PM6, BTP-eC9, L8-BO and AO1010 are as follows:

[0062]

[0063] The present application adds a hindered phenol antioxidant to a polymer donor and adds 1,8-diiodooctane or 1,3-dibromo-5-chlorobenzene to a non-fullerene acceptor to form an active layer with a thickness of 100-150 nm and high intrinsic stability and morphological stability, thereby improving the stability and photoelectric performance of an organic solar cell, and obtaining a highly efficient and stable quasi-planar organic solar cell.

[0064] The preferred amount of the hindered phenolic antioxidant is 2-8wt% of the amount of the polymer donor. The hindered phenolic antioxidant AO1010 has multiple hydroxyl binding sites and can react highly with superoxide radicals, thereby quenching free radicals and terminating free radical-induced chain degradation reactions, thereby improving the intrinsic stability of the active layer material. In addition, since the hindered phenolic antioxidant AO1010 has excellent thermal stability and obvious steric hindrance, it can effectively prevent excessive aggregation of donor and acceptor materials, thereby improving morphological stability.

[0065] In addition, the multiple hydroxyl groups in the hindered phenol antioxidant AO1010 can easily form hydrogen bonds with the fluorine atoms in the commonly used donor PM6, thereby enhancing the intermolecular interactions, thereby promoting the increase of the crystallinity of PM6, more orderly molecular stacking, and improved vertical phase separation morphology, which is beneficial to charge separation and transport.

[0066] In the present application, the transparent conductive substrate is preferably ITO glass; the hole transport layer material is preferably 2PACz; and the metal cathode layer material is preferably Ag or Al.

[0067] In this application, in order to achieve better technical effects, the non-fullerene acceptor and the electron layer transport material are adapted. When the non-fullerene acceptor is BTP-eC9, the electron transport layer material is PFN-Br, and the additive is 1,8-diiodooctane; when the non-fullerene acceptor is L8-BO, the electron transport layer material is PDINN, and the additive is 1,3-dibromo-5-chlorobenzene.

[0068] In a second aspect, the present application provides a method for preparing the above-mentioned efficient and stable quasi-planar organic solar cell, comprising:

[0069] S1, after cleaning the transparent conductive substrate, spin-coating an ethanol solution with a concentration of 2PACz on the surface of the substrate, and annealing the substrate to form a hole transport layer;

[0070] Specifically, a transparent conductive substrate, such as ITO glass, is ultrasonically cleaned with a detergent aqueous solution, acetone, and isopropyl alcohol in sequence, and then treated with a plasma cleaning machine.

[0071] Dissolve 2PACz in ethanol to prepare a solution with a concentration of 0.1-1.0 mg / mL; spin-coat the solution on the cleaned ITO glass surface at a speed of 3000 rpm for 30 seconds; then heat to 80-90°C and keep warm for 3-5 minutes for annealing.

[0072] S2, dissolving the polymer donor and the hindered phenol antioxidant in chloroform to prepare a donor solution. In the donor solution, the amount of the hindered phenol antioxidant is preferably 2-8wt% of the amount of the polymer donor, and the total concentration of the polymer donor and the hindered phenol antioxidant is 6-10mg / mL. Then, according to the selected non-fullerene acceptor material, different additives are adapted to prepare the acceptor solution, and then the active layer is prepared.

[0073] In the examples of the present application, two different non-fullerene acceptor materials are selected to prepare two active layers, which are respectively denoted as active layer A and active layer B.

[0074] Specifically, when BTP-eC9 is selected as the non-fullerene acceptor material, BTP-eC9 and 1,8-diiodooctane are dissolved in chloroform to prepare an acceptor solution A, the donor solution is first spin-coated on the surface of the hole transport layer, and then the acceptor solution A is spin-coated on the surface of the hole transport layer, and annealing is performed to obtain an active layer A; wherein the concentration of BTP-eC9 in the acceptor solution A is 6-12 mg / mL, and the volume of 1,8-diiodooctane is 0.25-0.5% of the volume of the acceptor solution A.

[0075] When L8-BO is selected as the non-fullerene acceptor material, L8-BO and 1,3-dibromo-5-chlorobenzene are dissolved in chloroform to prepare an acceptor solution B, the donor solution is first spin-coated on the surface of the hole transport layer, and then the acceptor solution B is spin-coated on the surface of the hole transport layer, and annealing is performed to obtain an active layer B. In the acceptor solution B, the concentration of L8-BO is 8-12 mg / mL, and the concentration of 1,3-dibromo-5-chlorobenzene is 10-15 mg / mL.

[0076] The donor solution is spin-coated at a speed of 2000-2500 rpm for 30-40 s; the acceptor solution A or acceptor solution B is spin-coated at a speed of 1500-2000 rpm for 30-40 s; after the acceptor solution A or acceptor solution B is spin-coated, the device is heated to 90-100° C. and kept warm for 5-10 minutes for annealing.

[0077] S3, dissolving PFN-Br in methanol to prepare an electron transport material solution A, and spin coating the solution on the surface of the active layer A to form an electron transport layer;

[0078] Specifically, when BTP-eC9 is selected as the non-fullerene acceptor material, PFN-Br is selected as the electron transport material of the electron transport layer corresponding to the prepared active layer A, and the concentration of PFN-Br is 0.1-1.0 mg / mL.

[0079] or,

[0080] PDINN is dissolved in methanol to prepare an electron transport material solution B, and the solution is spin-coated on the surface of the active layer B to form an electron transport layer;

[0081] Specifically, when L8-BO is selected as the non-fullerene acceptor material, the electron transport layer corresponding to the prepared active layer B is prepared such that PDINN is selected as the electron transport material, and the concentration of PDINN is 0.1-1.0 mg / mL.

[0082] The electron transport material solution A or the electron transport material solution B is spin-coated at a rotation speed of 3000-3500 rpm, and the spin-coating time is 30-40 s.

[0083] S4, evaporating a metal conductor on the surface of the electron transport layer to form a metal cathode layer, thereby obtaining a quasi-planar organic solar cell.

[0084] In the present application, the cathode layer metal is preferably silver or aluminum.

[0085] This application adopts a strategy of combining hindered phenol antioxidants as additives with a continuous spin coating method to obtain an active layer with high intrinsic stability and morphological stability, thereby improving the stability and photoelectric performance of organic solar cells, and thus obtaining a quasi-planar organic solar cell with high stability and high photoelectric performance. Its photoelectric conversion efficiency reaches 19.03%, and its stability is excellent, with good commercial prospects.

[0086] The present application is further described below by way of examples.

[0087] Example 1

[0088] This embodiment provides a method for preparing a quasi-planar organic solar cell, comprising:

[0089] S1, the ITO conductive glass sheet was sequentially subjected to ultrasonic cleaning of detergent solution, acetone and isopropanol for 40 min each, blown dry with a nitrogen gun, and then subjected to a plasma cleaning machine for 3 min;

[0090] The cleaned ITO glass sheet was transferred to a glove box, and an ethanol solution of 2PACz with a concentration of 0.5 mg / mL was spin-coated on the ITO glass sheet at a rotation speed of 3000 rpm for 30 seconds; then annealed at 80°C for 3 minutes to form a hole transport layer;

[0091] S2, dissolving PM6 and AO1010 in chloroform to prepare a donor solution with a concentration of 8 mg / mL, wherein the amount of AO1010 is 3 wt% of the amount of PM6; dissolving BTP-eC9 to which 1,8-diiodooctane is added at a volume percentage of 0.25% in chloroform to prepare a receptor solution with a concentration of 9 mg / mL;

[0092] The donor solution was spin-coated on the surface of the hole transport layer at a speed of 2500 rpm for 30 seconds; then the acceptor solution was spin-coated at a speed of 2000 rpm for 30 seconds. The thickness of the obtained mixed film was about 110 nm, forming a quasi-planar heterojunction film, i.e., the active layer; the device was annealed at 100° C. for 5 nanoseconds.

[0093] S3, dissolving PFN-Br in methanol to prepare a solution with a concentration of 0.5 mg / ml, and then spin-coating the solution on the active layer at a spin-coating speed of 3000 rpm for 30 seconds to form an electron transport layer.

[0094] S4, evaporating a metal Ag cathode layer on the electron transport layer to obtain a quasi-planar organic solar cell.

[0095] Example 2

[0096] This embodiment provides a method for preparing a quasi-planar organic solar cell, comprising:

[0097] S1, the ITO conductive glass sheet was sequentially subjected to ultrasonic cleaning of detergent solution, acetone and isopropanol for 40 min each, blown dry with a nitrogen gun, and then subjected to a plasma cleaning machine for 3 min;

[0098] The cleaned ITO glass sheet was transferred to a glove box, and an ethanol solution of 2PACz with a concentration of 0.5 mg / mL was spin-coated on the ITO glass sheet at a rotation speed of 3000 rpm for 30 seconds; then annealed at 80°C for 3 minutes to form a hole transport layer;

[0099] S2, dissolving PM6 and AO1010 in chloroform to prepare a donor solution with a concentration of 8 mg / mL, wherein the amount of AO1010 is 5wt% of the amount of PM6; dissolving BTP-eC9 to which 1,8-diiodooctane is added at a volume percentage of 0.25% in chloroform to prepare a receptor solution with a concentration of 9 mg / mL;

[0100] The donor solution was spin-coated on the surface of the hole transport layer at a speed of 2500 rpm for 30 seconds; then the acceptor solution was spin-coated at a speed of 2000 rpm for 30 seconds. The thickness of the obtained mixed film was about 110 nm, forming a quasi-planar heterojunction film, i.e., the active layer; the device was annealed at 100° C. for 5 nanoseconds.

[0101] S3, dissolving PFN-Br in methanol to prepare a solution with a concentration of 0.5 mg / ml, and then spin-coating the solution on the active layer at a spin-coating speed of 3000 rpm for 30 seconds to form an electron transport layer.

[0102] S4, evaporating a metal Ag cathode layer on the electron transport layer to obtain a quasi-planar organic solar cell.

[0103] Example 3

[0104] This embodiment provides a method for preparing a quasi-planar organic solar cell, comprising:

[0105] S1, the ITO conductive glass sheet was sequentially subjected to ultrasonic cleaning of detergent solution, acetone and isopropanol for 40 min each, blown dry with a nitrogen gun, and then subjected to a plasma cleaning machine for 3 min;

[0106] The cleaned ITO glass sheet was transferred to a glove box, and an ethanol solution of 2PACz with a concentration of 0.5 mg / mL was spin-coated on the ITO glass sheet at a rotation speed of 3000 rpm for 30 seconds; then annealed at 80°C for 3 minutes to form a hole transport layer;

[0107] S2, dissolving PM6 and AO1010 in chloroform to prepare a donor solution with a concentration of 8 mg / mL, wherein the amount of AO1010 is 8wt% of the amount of PM6; dissolving BTP-eC9 to which 1,8-diiodooctane is added at a volume percentage of 0.25% in chloroform to prepare a receptor solution with a concentration of 9 mg / mL;

[0108] The donor solution was spin-coated on the surface of the hole transport layer at a speed of 2500 rpm for 30 seconds; then the acceptor solution was spin-coated at a speed of 2000 rpm for 30 seconds. The thickness of the obtained mixed film was about 110 nm, forming a quasi-planar heterojunction film, i.e., the active layer; the device was annealed at 100° C. for 5 nanoseconds.

[0109] S3, dissolving PFN-Br in methanol to prepare a solution with a concentration of 0.5 mg / ml, and then spin-coating the solution on the active layer at a spin-coating speed of 3000 rpm for 30 seconds to form an electron transport layer.

[0110] S4, evaporating a metal Ag cathode layer on the electron transport layer to obtain a quasi-planar organic solar cell.

[0111] Example 4

[0112] This embodiment provides a method for preparing a quasi-planar organic solar cell, comprising:

[0113] S1, the ITO conductive glass sheet was sequentially subjected to ultrasonic cleaning of detergent solution, acetone and isopropanol for 40 min each, blown dry with a nitrogen gun, and then subjected to a plasma cleaning machine for 3 min;

[0114] The cleaned ITO glass sheet was transferred to a glove box, and an ethanol solution of 2PACz with a concentration of 0.5 mg / mL was spin-coated on the ITO glass sheet at a rotation speed of 3000 rpm for 30 seconds; then annealed at 80°C for 3 minutes to form a hole transport layer;

[0115] S2, dissolving PM6 and AO1010 in chloroform to prepare a donor solution with a concentration of 8 mg / mL, wherein the amount of AO1010 is 5wt% of the amount of PM6; dissolving 1,3-dibromo-5-chlorobenzene and L8-BO in chloroform to prepare a receptor solution with a concentration of 12 mg / mL of 1,3-dibromo-5-chlorobenzene and a concentration of 10 mg / mL of L8-BO;

[0116] The donor solution was spin-coated on the surface of the hole transport layer at a speed of 2500 rpm for 30 seconds; then the acceptor solution was spin-coated at a speed of 2000 rpm for 30 seconds. The thickness of the obtained mixed film was about 110 nm, forming a quasi-planar heterojunction film, i.e., the active layer; the device was annealed at 100° C. for 5 nanoseconds.

[0117] S3, dissolving PDINN in methanol to prepare a solution with a concentration of 1.5 mg / ml, and then spin-coating the solution on the active layer at a spin-coating speed of 3000 rpm for 30 seconds to form an electron transport layer.

[0118] S4, evaporating a metal Ag cathode layer on the electron transport layer to obtain a quasi-planar organic solar cell.

[0119] Comparative Example 1

[0120] The difference between Comparative Example 1 and Example 1 is that AO1010 is not added to the donor solution, and the rest is the same as Example 1.

[0121] Comparative Example 2

[0122] The difference between Comparative Example 2 and Example 4 is that AO1010 is not added to the donor solution, and the rest is the same as Example 4.

[0123] The UV-visible absorption spectra of the polymer donor PM6, the non-fullerene acceptors BTP-eC9 and L8-BO, and the antioxidant AO1010 used in the active layer of the embodiment were tested. The results are as follows: Figure 1 As shown. Figure 1 It can be seen that A01010 does not absorb sunlight, while the donor PM6 and the acceptor BTP-eC9 or L8-BO have good complementary absorption.

[0124] The photoelectric performance of the quasi-planar organic solar cell devices prepared in Examples 1-4 and Comparative Examples 1-2 was tested by the following method:

[0125] The selected light source is AM1.5G, and the sunlight intensity is 100mW / cm 2 The intensity of the light source was tested and calibrated by a standard silicon cell, and the test instrument was a Keithley 2400 Source Meter. The photoelectric performance of the organic solar cell was tested, including the open circuit voltage (V OC ), short circuit current (J SC ), fill factor (FF) and power conversion efficiency (PCE), where: PCE = V OC *J SC *FF / Pin (Pin is the intensity of incident light).

[0126] Among them, the current-voltage curves of the binary and ternary quasi-planar organic solar cells based on PM6 / BTP-eC9, such as the organic solar cells of Example 2 and Comparative Example 1 under illumination are as follows: Figure 2 As shown, the current density of Example 2 is higher than that of Comparative Example 1; the current-voltage curves of binary and ternary quasi-planar organic solar cells based on PM6 / L8-BO, such as the organic solar cells of Example 4 and Comparative Example 2 under illumination are shown in Figure 3 As shown, the current density of Example 4 is higher than that of Comparative Example 2. The quasi-planar organic solar cell prepared by introducing hindered phenol antioxidants in the present application has improved photoelectric performance.

[0127] The test results of the quasi-planar organic solar cells prepared in Examples 1-4 and Comparative Examples 1-2 are shown in Table 1.

[0128] Table 1 Different devices at AM1.5G, 100mW / cm 2 Photoelectric performance parameters under illumination

[0129]

[0130]

[0131] From the test results in Table 1, it can be seen that when antioxidants are added as additives to PM6, the short-circuit current and fill factor of the obtained ternary quasi-planar organic solar cells are improved compared with the binary system quasi-planar organic solar cells, indicating that the exciton dissociation and charge transfer efficiency are improved, and the charge recombination is suppressed. When AO1010 accounts for 5% of the donor mass, the effect of the prepared quasi-planar organic solar cell reaches the best. Among them, when 5wt% of AO1010 is added to PM6 / L8-BO, the energy conversion efficiency can reach 19.03%, which is much higher than the 18.02% of its binary system.

[0132] The storage stability test was performed on the quasi-planar organic solar cells prepared in Example 4 and Comparative Example 4, and the specific method was as follows:

[0133] At 25°C and in a nitrogen atmosphere, the quasi-planar device was tested for its energy conversion efficiency every 100 hours using a standard solar simulator, and the obtained energy conversion efficiency was normalized and plotted, as shown in Figure 2. Figure 4 shown.

[0134] from Figure 4It can be seen that after adding A01010, the storage stability of the device is significantly improved. The T80 life extrapolation value of the device based on PM6+AO1010 (5%) / L8-BO in Example 4 exceeds 3000 hours, which is significantly better than the device without AO1010 in Comparative Example 2, indicating that the addition of the antioxidant greatly improves the efficiency of the device and effectively improves the stability of the device.

[0135] Although the present application has been described in detail in general terms and in specific embodiments in this specification, it is obvious to those skilled in the art that some modifications or improvements may be made to the present application. Therefore, these modifications or improvements made without departing from the spirit of the present application are within the scope of protection claimed in the present application.

Claims

1. A highly efficient and stable quasi-planar organic solar cell, characterized in that: It includes, from bottom to top, a transparent conductive substrate, a hole transport layer, an active layer, an electron transport layer and a metal cathode layer; The active layer includes a polymer donor layer with a hindered phenol antioxidant added thereto, which is spin-coated on a hole transport layer, and a non-fullerene acceptor layer containing an additive, which is spin-coated on the polymer donor layer.

2. The efficient and stable quasi-planar organic solar cell according to claim 1, characterized in that: The polymer donor is any one of PM6, PM7 or D18; The non-fullerene acceptor is BTP-eC9 or L8-BO; The hindered phenol antioxidant is any one of antioxidants AO1010, AO245 or AO3114; The additive is 1,8-diiodooctane or 1,3-dibromo-5-chlorobenzene.

3. The efficient and stable quasi-planar organic solar cell according to claim 1, characterized in that: The amount of the hindered phenol antioxidant used is 2-8 wt % of the amount of the polymer donor used.

4. The efficient and stable quasi-planar organic solar cell according to claim 1, characterized in that: The thickness of the active layer is 100-150 nm.

5. The efficient and stable quasi-planar organic solar cell according to claim 2, characterized in that: The transparent conductive substrate is ITO glass; The hole transport layer material is 2PACz; The metal cathode layer material is Ag or Al; When the non-fullerene acceptor is BTP-eC9, the electron transport layer material is PFN-Br, and the additive is 1,8-diiodooctane; When the non-fullerene acceptor is L8-BO, the electron transport layer material is PDINN, and the additive is 1,3-dibromo-5-chlorobenzene.

6. The method for preparing a highly efficient and stable quasi-planar organic solar cell according to claim 5, characterized in that: include: S1, after cleaning the transparent conductive substrate, spin-coating an ethanol solution with a concentration of 2PACz on the surface of the substrate, and annealing the substrate to form a hole transport layer; S2, dissolving the polymer donor and the hindered phenol antioxidant in chloroform to prepare a donor solution; BTP-eC9 and 1,8-diiodooctane were dissolved in chloroform to prepare acceptor solution A. The donor solution was first spin-coated on the surface of the hole transport layer, and then the acceptor solution A was spin-coated on the surface of the hole transport layer. After annealing, an active layer A was obtained. or, L8-BO and 1,3-dibromo-5-chlorobenzene were dissolved in chloroform to prepare acceptor solution B. The donor solution was first spin-coated on the surface of the hole transport layer, and then the acceptor solution B was spin-coated on the surface of the hole transport layer. After annealing, an active layer B was obtained. S3, dissolving PFN-Br in methanol to prepare an electron transport material solution A, and spin coating the solution on the surface of the active layer A to form an electron transport layer; Alternatively, PDINN is dissolved in methanol to prepare an electron transport material solution B, and the solution is spin-coated on the surface of the active layer B to form an electron transport layer; S4, evaporating a metal conductor on the surface of the electron transport layer to form a metal cathode layer, thereby obtaining a quasi-planar organic solar cell.

7. The preparation method according to claim 6, characterized in that: In S2, the donor solution is spin-coated at a speed of 2000-2500 rpm and the spin-coating time is 30-40 s; The spin speed of the receptor solution A or receptor solution B is 1500-2000 rpm, and the spin coating time is 30-40 s; The annealing temperature is 90-100°C, and the annealing time is 5-10 minutes.

8. The preparation method according to claim 6, characterized in that: In S1, the spin coating speed of the 2PACz ethanol solution is 3000 rpm, and the spin coating time is 30 seconds; the annealing temperature is 80-90°C, and the time is 3-5 minutes; In S3, the electron transport material solution A or the electron transport material solution B is spin-coated at a rotation speed of 3000-3500 rpm, and the spin-coating time is 30-40 s.

9. The preparation method according to claim 6, characterized in that: The concentration of the 2PACz ethanol solution is 0.1-1.0 mg / mL; In the donor solution, the total concentration of the polymer donor and the hindered phenol antioxidant is 6-10 mg / mL; In the receptor solution A, the concentration of BTP-eC9 is 6-12 mg / mL; In the receptor solution B, the concentration of L8-BO is 8-12 mg / mL; In the electron transport material solution A, the concentration of PFN-Br is 0.1-1.0 mg / mL; In the electron transport material solution B, the concentration of PDINN is 0.1-1.0 mg / mL.

10. The preparation method according to claim 6, characterized in that: The volume of the 1,8-diiodooctane is 0.25-0.5% of the volume of the receptor solution A; In the receptor solution B, the concentration of 1,3-dibromo-5-chlorobenzene was 10-15 mg / mL.

Citation Information

Patent Citations

  • Organic solar cell based on thermal substrate process and preparation method and application thereof

    CN116209285A

  • Organic solar cell based on chlorophyll derivative and preparation method thereof

    CN117202747A

  • Organic solar cell active layer based on liquid crystal molecules and application thereof

    CN117615586A

  • Organic photovoltaic cell

    US20120216866A1